1978
DOI: 10.1159/000119779
|View full text |Cite
|
Sign up to set email alerts
|

The Central (Spinal) Canal in Congenital Murine Hydrocephalus: Morphological and Physiological Aspects

Abstract: Obstruction of cerebrospinal fluid pathways produces changes in the parenchyma of the brain and spinal cord. A murine model of hydrocephalus (hy-3) used to study changes in the central canal of the spinal cord and these changes are correlated with events occurring in the intracranial compartment. The central canal is enlarged and subependymal interstitial edema is produced by cerebrospinal fluid at the same time as the intracranial ventricular system is expanding. Plugging of the obex results in collapse of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1979
1979
2000
2000

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 14 publications
(16 reference statements)
0
4
0
Order By: Relevance
“…These changes are similar regardless of the cause of hydrocephalus [1], being induced mainly by increased intraventricular pressure. In the spinal central canal, however, the ependyma may be exposed to a variety of cerebrospinal fluid pressures depending on the cause of hydrocephalus, resulting in different ependymal abnormalities according to the pathogenesis of ventricular dilatation [16,19,20,22,29,40].…”
Section: Introductionmentioning
confidence: 99%
“…These changes are similar regardless of the cause of hydrocephalus [1], being induced mainly by increased intraventricular pressure. In the spinal central canal, however, the ependyma may be exposed to a variety of cerebrospinal fluid pressures depending on the cause of hydrocephalus, resulting in different ependymal abnormalities according to the pathogenesis of ventricular dilatation [16,19,20,22,29,40].…”
Section: Introductionmentioning
confidence: 99%
“…Neither author cited specific information regarding the histologie findings or details of the selection process that resulted in this animal model of syringomyelia. Kuwamura et al (1978) reported the morphologic and physiologic aspects of the dilated central canal in congenitally hydrocéphalie mice. Although the animals' short life span limited their use as a model of human syringomyelia, histopathologic examination of the spinal cord subependymal tissue layers after intrathecal injection of ferritin suggested that the increased extracellular space in this area was the result of the increased CSF hydrodynamics.…”
Section: Histopathology and Pathogenesis Of Syringomyeliamentioning
confidence: 99%
“…Changes in the central canal of the spinal cord are correlated with events occurring in the intracranial compartment [2]. The central canal enlarges and subependymal interstitial edema is produced by cerebrospinal fluid at the same time as these events take place within the ventricular system ( fig.…”
Section: The Central Canal In Murine Hydrocephalusmentioning
confidence: 99%